PSIKOEDUKASI “GURU TANGGUH” UNTUK MENINGKATKAN REGULASI EMOSI PADA GURU - Riana Sahrani; Dastin Imanuel; Olivia Aldisa; Tania Mursalim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Teachers have an important role in creating the emotional atmosphere of the classroom; nevertheless, many teachers still encounter challenges in regulating both their own emotions and those of their students. Reactive emotional behavior and the tendency to suppress emotions can contribute to emotional fatigue among teachers and may reduce the effectiveness of the learning process. In response to this issue, this activity was conducted to analyze the impact of the psychoeducational program entitled “Resilient Teachers: The Art of Responding to Emotions Wisely” on teachers’ emotion regulation skills at School X. The study applied a simple mixed-method approach with a one-group pretest–posttest design, supported by interviews conducted before and after the psychoeducation sessions. Quantitative data were collected using the Emotion Regulation Questionnaire–Short Form (ERQ-S), while qualitative information was gathered through semi-structured interviews with three teachers. The findings showed an increase in the average cognitive reappraisal score from 6.283 in the pretest to 6.456 in the posttest, alongside a decrease in the average expressive suppression score from 5.533 to 5.474. These results were supported by interview findings that demonstrated a change in teachers’ responses from reactive tendencies to more reflective behaviors, indicated by greater emotional awareness, the practice of pausing before reacting, and the ability to reinterpret classroom situations cognitively. Overall, the “Resilient Teachers” psychoeducation program positively contributed to improving teachers’ understanding and implementation of more adaptive emotion regulation strategies, which may support teacher well-being and promote a healthier classroom environment. ABSTRAK Guru memegang peranan penting dalam membentuk iklim emosional di kelas, tetapi dalam praktiknya masih banyak guru yang mengalami kesulitan dalam mengelola emosi, baik emosi pribadi maupun emosi peserta didik. Respons emosional yang cenderung reaktif serta dominasi penekanan emosi berpotensi meningkatkan kelelahan emosional guru dan berdampak pada kualitas pembelajaran. Berdasarkan kondisi tersebut, kegiatan ini bertujuan untuk menganalisis dampak psikoedukasi “Guru Tangguh: Seni Merespons Emosi dengan Bijak” terhadap kemampuan regulasi emosi guru di Sekolah X. Kegiatan ini menggunakan pendekatan mixed-method sederhana dengan desain one group pretest–posttest yang dipadukan dengan wawancara sebelum dan sesudah pelaksanaan psikoedukasi. Asesmen kuantitatif dilakukan menggunakan Emotion Regulation Questionnaire–Short Form (ERQ-S), sedangkan data kualitatif diperoleh melalui wawancara semi-terstruktur terhadap tiga orang guru. Hasil asesmen menunjukkan adanya peningkatan rata-rata skor cognitive reappraisal dari 6,283 pada pretest menjadi 6,456 pada posttest, serta penurunan rata-rata skor expressive suppression dari 5,533 menjadi 5,474. Temuan tersebut sejalan dengan hasil wawancara yang memperlihatkan adanya perubahan respons guru dari pola yang reaktif menjadi lebih reflektif, ditandai dengan meningkatnya kesadaran emosi, kemampuan memberi jeda sebelum merespons, serta kemampuan memaknai ulang situasi di kelas. Secara keseluruhan, psikoedukasi “Guru Tangguh” memberikan kontribusi positif dalam meningkatkan pemahaman dan penerapan strategi regulasi emosi yang lebih adaptif pada guru, sehingga berpotensi mendukung kesejahteraan guru dan menciptakan iklim pembelajaran yang lebih sehat.